"Don't bother about me." The grief and mental health of bereaved adolescents. Issue 10 (26th November 2018) - Andriessen, Karl; Mowll, Jane; Lobb, Elizabeth; Draper, Brian; Dudley, Michael; Mitchell, Philip B.
ABSTRACT: Death of a relative or friend is a potentially disruptive event in the lives of adolescents. To provide targeted help, it is crucial to understand their grief and mental health experiences. Thematic analysis of 39 semistructured telephone interviews yielded two themes: Grieving apart together and Personal growth . High self-reliance and selective sharing were common. Feelings of guilt and "why" questions seemed more pronounced among the suicide bereaved. There was strong evidence of personal growth, increased maturity, and capacity to deal with personal mental health/suicidality. Despite its devastating effects, experiencing a death can be a catalyst for positive mental health.